Harvest date affects aronia juice polyphenols, sugars, and antioxidant activity, but not anthocyanin stability. (15th November 2015) - Bolling, Bradley W.; Taheri, Rod; Pei, Ruisong; Kranz, Sarah; Yu, Mo; Durocher, Shelley N.; Brand, Mark H.
Highlights: Aronia juice anthocyanins peaked at mid-harvest. Aronia juice sorbitol increased 40% throughout the harvest period. Aronia anthocyanin pigmentation was stabilized by quercetin, sorbitol, and β-cyclodextrin. Sorbitol and citric acid inhibited DPPH antioxidant capacity of aronia juice. Abstract: The goal of this work was to characterize how the date of harvest of 'Viking' aronia berry impacts juice pigmentation, sugars, and antioxidant activity. Aronia juice anthocyanins doubled at the fifth week of the harvest, and then decreased. Juice hydroxycinnamic acids decreased 33% from the first week, while proanthocyanidins increased 64%. Juice fructose and glucose plateaued at the fourth week, but sorbitol increased 40% to the seventh harvest week. Aronia juice pigment density increased due to anthocyanin concentration, and polyphenol copigmentation did not significantly affect juice pigmentation. Anthocyanin stability at pH 4.5 was similar between weeks. However, addition of quercetin, sorbitol, and chlorogenic acid to aronia anthocyanins inhibited pH-induced loss of color. Sorbitol and citric acid may be partially responsible for weekly variation in antioxidant activity, as addition of these agents inhibited DPPH scavenging 13–30%. Thus, aronia polyphenol and non-polyphenol components contribute to its colorant and antioxidant functionality.